2020
DOI: 10.18034/gdeb.v9i2.511
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Nature of Job Satisfaction Level: A Study on Private Bank Employees in Bangladesh

Abstract: The purpose of this study is to assess the nature of the job satisfaction level of private bank employees in Bangladesh. It used a semi-structured questionnaire which contains both pre-coded and open-ended questions. All questions were rated with the Likert 5-point scale. A Chi-square test was used to assess the relationship between independent and dependent variables. In this study, a significant inter-class relationship was observed between demographic characteristics namely sex, age, designation, salary, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In contrast to our nation, people in developed and newly industrialized countries are more interested in private sectors (Cho et al, 2010;Danzer, 2019) because these sectors offer higher financial and other benefits than the government sector (Cho et al, 2010;Hasan et al, 2020).…”
Section: Introductionmentioning
confidence: 83%
“…In contrast to our nation, people in developed and newly industrialized countries are more interested in private sectors (Cho et al, 2010;Danzer, 2019) because these sectors offer higher financial and other benefits than the government sector (Cho et al, 2010;Hasan et al, 2020).…”
Section: Introductionmentioning
confidence: 83%
“…From the words of Hasan et al (2020) promotion enables employees to change their levels of work positions to higher ones. Studies have shown that organizations that fairly promote their workers based on merit stimulate the job satisfaction of their employees (Muhammad & Akhter, 2010, Hasan, Afrin, Rahman & Ahmed, 2020. Promotion opportunities stimulate staff to work hard toward the improvement and growth of firms.…”
Section: Promotionmentioning
confidence: 99%
“…Mobile phone technology has become the most potential and well-suited channel for financial inclusion (Asfaw, 2015). Mobile phone use for financial inclusion is prevalent, and most people need more banking facilities (Sumanjeet, 2010;Hasan et al, 2020;Hossain & Haque, 2014).…”
Section: Introductionmentioning
confidence: 99%